Subordinasi dan Sudut Pandang Perempuan Suku Malind Marga Mahuze dalam Film the Mahuzes (2015): a Feminist Standpoint Theory - Arfiani, Dini (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Abstract: Documentary films are one of the most suitable media to be used as a reference in seeing reality. Like the reality of subordination and women's point of view in The Mahuzes. In general, this film tells the story of the conflict that occurred between the Malind clan Mahuze in Merauke and corporations that entered their territory through the Merauke Integrated Food and Energy Estate (MIFEE) program, besides that there were horizontal conflicts between tribal members. This study aims to analyze the form of subordination and women's point of view seeing the problems of indigenous peoples dealing with corporations which are shown by the documentary film The Mahuzes in the perspective of Feminist Standpoint Theory. This study uses a qualitative approach and a critical paradigm by collecting data from various relevant sources. Events involving or relating to women were analyzed using three basic concepts of Feminist Standpoint Theory, namely standpoint, situated knowledge, and sexual division of labour. The results of the study indicate that women in The Mahuzes are a marginalized group, forced to take responsibility for the domestic space, and are limited to take part in the public sphere. Even so, they have a broad and comprehensive perspective in viewing horizontal conflicts between clan members and vertically between clans and corporations. Keywords: Subordinate; Feminist Standpoint; MIFEE; The Mahuze Abstrak: Film dokumenter menjadi salah satu media yang paling sesuai untuk dijadikan sebagai rujukan dalam melihat realitas. Seperti realitas subordinasi dan sudut pandang perempuan dalam The Mahuzes. Film ini, secara garis besar berkisah tentang konflik yang terjadi antara suku Malind marga Mahuze di Merauke dengan korporasi yang masuk ke wilayah mereka melalui program Merauke Integrated Food and Energy Estate (MIFEE), selain itu terdapat konflik horizontal antar anggota suku. Penelitian ini bertujuan untuk menganalisis bentuk subordinasi dan sudut pandang perempuan melihat permasalahan masyarakat adat berhadapan dengan korporasi yang ditampilkan oleh film dokumenter The Mahuzes dalam perspektif Feminist Standpoint Theory. Penelitian ini menggunakan pendekatan kualitatif dan paradigma kritis dengan mengumpulkan data dari berbagai sumber yang relevan. Agedan-agedan yang melibatkan atau berkaitan dengan perempuan dianalisis dengan menggunakan tiga konsep dasar Feminist Standpoint Theory, yaitu standpoint, situated knowledge, dan sexual division of labour. Hasil penelitian menunjukkan bahwa, perempuan dalam The Mahuzes merupakan kelompok yang terpinggirkan, dipaksa untuk bertanggung jawab pada ruang domestik, dan terbatas untuk berkiprah di ruang publik. Meskipun begitu, mereka memiliki sudut pandang yang luas dan menyeluruh dalam melihat konflik horizontal antar anggota marga maupun vertikal antara marga dan korporasi. Kata kunci: Subordinasi; Feminist Standpoint; MIFEE; The Mahuze